A Hospital Based Study of Association of Chronic Spontaneous Urticaria with Autologous Serum Skin Test - Uma Giri; Bhaskar MM Kayastha; Nabin Bhakta Shakya (Nepal Journal of Dermatology, Venereology & Leprology)
Introduction: Chronic Spontaneous Urticaria (CSU), is spontaneous occurrence of wheals for more than 6 weeks. CSU patients with autoreactivity as indicated by positive Autologous serum skin test (ASST) have severe disease requiring higher doses of antihistamines and even immunomodulatory agents.